Pyogenic Liver Abscess. A Case Report - Miguel Ángel Serra Valdés; Yordanka Yamilé Aleaga Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2013)
Liver abscesses account for 13% of all abdominal abscesses and 48% of those occurring in the viscera. The bacterial or pyogenic liver abscesses are the most frequent. A case of a 34-year-old woman of mixed race with history of gallstones (2011), extrahepatic obstructive jaundice caused by cholelithiasis (May 2012), cholangitis after endoscopic retrograde cholangiopancreatography (ERCP) and cholecystectomy (August 2012) due to gallstones is presented. In September 2012, she began suffering from high fever with chills every day, usually in the evenings. In addition, she presented night sweats, loss of appetite, weight loss, nausea and pain in the right upper quadrant of the abdomen which was sharp, permanent and annoying sometimes. The signs and symptoms, history, ultrasound scan and multislice computed tomography confirmed the diagnosis of pyogenic liver abscess. The risk factors leading to the infection were well-identified. The patient progressed satisfactorily with the medical treatment provided.